The Role of Elections in Improving Democracy in Indonesia - Rahmah, Annisatur; Ulfa, Salsabila Azhara; Marlisa, Sela; Azharum, Sandrina Titha; Susanti, Emilia (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
From a linguistic (etymological) point of view, demokr comes from the Greek demos which means people and cratos or cratein which means government. So, in linguistic terms, democracy is the government of the people or the power of the people. The concept of democracy was born from ancient Greece and was practiced in state life between the 4th century BC to the 6th century AD. The democracy practiced at that time was direct democracy, meaning The people's right to make political decisions is exercised directly by all the people or citizens of the State. This was possible because Greece at that time was a city state (polis) whose population was limited to one city and the surrounding area, with a population of around 300,000 people. Even though there was involvement of all citizens, there were still restrictions, for example children, women and slaves had no right to participate in government.